Hybrid composites of aligned discontinuous carbon fibers and self-reinforced polypropylene under tensile loading. (August 2019) - Tang, Jun; Swolfs, Yentl; Longana, Marco L.; Yu, HaNa; Wisnom, Michael R.; Lomov, Stepan V.; Gorbatikh, Larissa
Abstract: Highly aligned discontinuous fiber composites have demonstrated mechanical properties comparable to those of unidirectional continuous fiber composites. However, their ductility is still limited by the intrinsic brittleness of the fibers and stress concentrations at the fiber ends. Hybridization of aligned discontinuous carbon fibers (ADCF) with self-reinforced polypropylene (SRPP) is a promising strategy to achieve a balanced performance in terms of stiffness, provided by the ADCF, and ductility, delivered by SRPP. The current work focuses on interlayer hybridization of these materials and their tensile behavior as a function of different material parameters. Effects of the carbon layer thickness, carbon/SRPP layer thickness ratio, layer dispersion and interface adhesion are investigated. The carbon fiber misalignment is characterized using X-ray computed tomography to predict the modulus of the aligned discontinuous carbon fiber layer. The hybrids exhibit a gradual tensile failure with high pseudo-ductile strain of above 10% facilitated by multiple carbon layer failures (layer fragmentation) and dispersed delaminations. At the microscopic scale, the carbon layer fails mainly through interfacial debonding and fiber pull-out.